Sustainable livelihood strategies of fishing communities in Marine Protected Area (MPA), Sabah, Malaysia - Jalihah Md Shah; Md Sayed Uddin; Rosazman Hussin; Diana Demiyah Mohd Hamdan; Dzurizah Ibrahim; Norina Natasha; Norina Natasha Ag Ijuwan (Macrothink Institute, 2022)
Marine Protected Areas (MPA) are an important management tool adopted by most the nations for conservation of marine and ﬁsheries to save marine ecosystems that are in danger of being overexploited. Malaysia is no exception as coastal regions of Malaysia is prospective for fisheries and many others development activities. The MPAs have an immense impact on people’s livelihood. This study aims to understand the livelihoods of the fishing community in MPAs, Marudu Bay, Sabah, Malaysia. It is guided by the Sustainable Livelihoods Framework (SLF) to analyze the indicators of sustainable livelihood capitals and strategies of the MPAs fishing communities. This study uses a qualitative approach. In-depth interviews with five informants were chosen for the data collection using the purposive sampling technique. According to the findings, the informant’s human capital, such as education, health, leadership, skills, and training, has not yet reached a level that could offer a reasonable standard of living and livelihood for the research site's population. Residents of the study sites do not have many options for increasing their household income level. In many locations, fishing is a less appealing occupation. The study provided recommendations and strategies on how to further develop and sustain the livelihood of the fisheries community in MPAs, Sabah.